STANDARD COSTS AS A FIRST STEP TO PROBABILISTIC CONTROL: A THEORETICAL JUSTIFICATION, AND EXTENSION AND IMPLICATION. - Zannetos, Zenon S. (The Accounting Review, 1964)
Abstract One of the most important advances in the field of managerial accounting has been the development of the notion of the standard cost system. The use of such a system, however, has thus far been limited not because of any limitations inherent in the system itself, but because accountants have failed to appreciate its versatility and exploit it for managerial control and decision making. By definition costs that are not quantitatively traceable to products or operations for every unit of service used at a particular moment of time, are some type of joint costs. This implies complementarities between products and operations at any moment of time and over lime, and a lot of uncertainty in planning and control. The longer the time span over which such complementarities exist the greater the difficulty not only because one cannot predict as well, which is a great impediment to decision making, but also because the statistical population from which one needs to draw for generalizations is small. Furthermore, to the extent that these decisions are made discontinuously and infrequently, one cannot depend on the manager's memory for all the relevant inputs to subsequent decisions of similar nature.